COVID-19 Vaccine Intentions and Perceptions Among Public School Staff of the Greater Vancouver Metropolitan Area, British Columbia, Canada - Watts, Allison W.; Hutchison, Sarah M.; Bettinger, Julie A.; Gadermann, Anne; Oberle, Eva; Oberlander, Tim F.; Goldfarb, David M.; Lavoie, Pascal M.; Mâsse, Louise C. (Frontiers in Public Health, 2022)
Background: The purpose of this study was to explore factors associated with COVID-19 vaccine intentions among school staff as high vaccine uptake is essential to ensure schools return to normal activities. Methods: Staff (e.g., teachers, administrators, student support workers) from three urban school districts in the Greater Vancouver Area of British Columbia, Canada completed a survey between February and June 2021 (n=2393) on COVID-19 vaccine intentions and perceptions (i.e., acceptance of routine vaccines, benefits and risks of vaccination, susceptibility to, and severity of COVID-19, recommendation by authority figures, information mistrust and conspiracy beliefs) as part of a COVID-19 seroprevalence study. Confirmatory factor analysis followed by multiple logistic regression models adjusting for relevant covariates were used to identify vaccine perceptions uniquely associated with a) intention to get the COVID-19 vaccine (intention), and b) intention to get vaccinated right away (urgency). Results: In total, 95.4% of participants of the seroprevalence study completed the vaccine intentions questionnaire, corresponding to 17.7% of the target population. Vaccine intention was associated with staff who valued expert recommendations (AOR=10.5, 95% CI=7.39-14.90) accepted routine vaccines (AOR=1.94, 95% CI=1.26-2.98) and perceived higher benefits (AOR=1.29, 95% CI=1.01-1.65) and lower safety risks of vaccination (AOR=0.40, 95% CI=0.29-0.54). Comparable associations were found with vaccine urgency. Perceived susceptibility to the COVID-19 virus was uniquely associated with vaccine urgency (AOR=1.30, 95% CI=1.05-1.61). A significant interaction effect (p=0.01) revealed that staff who expressed mistrust in COVID-19 information intended to get vaccinated only if they also perceived high benefits of vaccination. Conclusions: Education about the risks and benefits of COVID-19 vaccines from a trusted source had the strongest relationship with vaccine intentions among this occupational group. Notably, those who expressed mistrust in information still intended to get vaccinated if they also perceived strong benefits of the vaccine.